Berpikir kritis matematis dengan kahoot - Elis Maulidah; Agus Hikmat Syaf; Tika Karlina Rachmawati; Hamdan Sugilar (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2020)
The purpose of this study was to determine the improvement of students' mathematical critical thinking skills after obtaining mathematics learning using Kahoot-based Spontaneous Group Discussion models. The research method used was a quasi-experimental method with the Nonequivalent Control group Design. The subjects of this study were class X students in one of Bandung's high schools. Data obtained using a research instrument in the form of a test. Based on the results of research and processing of N-Gain data, it was found that the average increase in students' mathematical critical thinking skills (N-gain) after obtaining mathematics learning using the Spontaneous Group Discussion (SGD) model based on kahoot was 0.76 and the average N- The gain in conventional learning is 0.56. It can be concluded that increasing students' mathematical critical thinking skills using the Spontaneous Group Discussion (SGD) model based on kahoot is better than conventional learning